Clinical researchLong-term survival of endometrioid endometrial cancer patients - Gottwald, Leszek; Pluta, Piotr; Piekarski, Janusz; Spych, Michał; Hendzel, Katarzyna; Topczewska-Tylinska, Katarzyna; Nejc, Dariusz; Bibik, Robert; Korczyński, Jerzy; Ciałkowska-Rysz, Aleksandra (Archives of Medical Science, 2010)
Introduction : To establish risk factors for onset and progression of endometrioid endometrial cancer still remains the aim of scientists. The aim of the study was to determine disease-free survival (DFS) and overall survival (OS) in women with endometrioid endometrial cancer. Material and methods : A retrospective review of 142 patients with endometrioid endometrial cancer after surgery treated with adjuvant radiotherapy and/or chemotherapy in the Regional Cancer Centre in Lodz between 2002 and 2004 was performed. Clinical and pathological data were correlated with clinical outcome and survival. Results : In 3 patients (2.1%) clinical progression was diagnosed during the treatment. In 23 patients (16.7%) after primary remission, relapse was diagnosed 2-56 months after treatment. DFS and OS were 81.7% and 83.1% respectively. Better DFS significantly correlated with larger number of pregnancies (> 1), stage I of the disease and optimal surgery. Lower stage of disease, pelvic lymph node dissection, optimal surgery and depth of myometrial infiltration  50% were independent prognostic factors for better OS. Conclusions : The results of our study provided significant evidence that early detection of endometrioid endometrial cancer enables optimal surgery. It reduces the indications for adjuvant therapy in stage I of the disease, and makes the prognosis significantly better. Other clinical and pathological factors such as numerous pregnancies, pelvic lymphadenectomy, and depth of myometrial infiltration, although important, are of less significance. Further prospective, randomized studies are necessary to prove the role of these factors.